MICROSOMACANTHUS HOPKINSI (EUCESTODA, HYMENOLEPIDIDAE) IN NETTA PEPOSACA (AVES, ANATIDAE) IN SOUTH AMERICA - Silveira, Eliane F. (2010)
The rosy-billed pochard, Netta peposaca (Vieillot, 1816), is a migratory bird that inhabits wetlands which have the surface covered by abundant vegetation, but also being found in lagoons or rice plantations. One hundred sixty-nine rosy-billed pochards, N. peposaca, were examined for helminths in the Municipalities of Santa Vitória do Palmar and Jaguarão, State of Rio Grande do Sul, Brazil (wintering site) and Alvear, Corrientes Province, northern Argentina (nesting site). Samples were obtained in 2002 and 2004. Birds were frozen in dry ice after collection. During necropsy they were categorized according to sex and maturity, either adult or juvenile. The cestode Microsomacanthus hopkinsi (Schiller, 1951) Spasskaia, 1966 was found in the anterior portion of caeca. Prevalence was 60.9% and mean infection 42.9, while the intensity of infection was 1 to 418 helminths/ host. The high prevalence and intensity of infection may be related to the reproductive strategy of the species that releases the eggs in the form of a single chain.